Hand vein pattern recognition - Nguyen, Canh Lich. (2012)
For authentication technologies such as password, keys or cards, all that known during the authenticating process is that the correct information presented to the system, not who is holding it. Any unauthorized person can bypass the security system if possesses or known the information. That issue raises a demand for higher reliable security system. Biometrics system, on the other hand, is automated recognition of individual based on their biological or behavior characteristics. Unique human characteristic such as fingerprint, iris, voice, hand geometry and many are used to verify an identity. Thus in most case, only the authorized person holds the correct information is to be authenticated.